2022
DOI: 10.1093/humupd/dmac037
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2, fertility and assisted reproduction

Abstract: BACKGROUND In 2020, SARS-CoV-2 and the COVID-19 pandemic had a huge impact on the access to and provision of ART treatments. Gradually, knowledge of the virus and its transmission has become available, allowing ART activities to resume. Still, questions on the impact of the virus on human gametes and fertility remain. OBJECTIVE AND RATIONALE This article summarizes published data, aiming to clarify the impact of SARS-CoV-2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
10

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 188 publications
(248 reference statements)
2
55
0
10
Order By: Relevance
“…Angiotensin-converting enzyme 2 (ACE2) and transmembrane protease serine subtype 2 (TMPRSS2) are expressed in the reproduction system in both males and females 1 ; therefore, reproductive function is theoretically vulnerable to SARS-CoV-2 infection, and many studies 2,3 have explored the possible effect of SARS-CoV-2 infection on the human reproductive system. A recent review 4 summarized published data and clarified the effect of SARS-CoV-2 and COVID-19 on human fertility and assisted reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin-converting enzyme 2 (ACE2) and transmembrane protease serine subtype 2 (TMPRSS2) are expressed in the reproduction system in both males and females 1 ; therefore, reproductive function is theoretically vulnerable to SARS-CoV-2 infection, and many studies 2,3 have explored the possible effect of SARS-CoV-2 infection on the human reproductive system. A recent review 4 summarized published data and clarified the effect of SARS-CoV-2 and COVID-19 on human fertility and assisted reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Several pathogens, such as hepatitis virus, human immunode ciency virus, and Zika virus [27], may have variable impacts on the physiopathology of the reproductive organs, leading to infertility or poor ART outcomes [28]. Therefore, when the new SARS-CoV-2 virus emerged and spread globally, researchers focused on the impact of infection with this virus on human reproduction and ART outcomes [5]. The effects of SARS-CoV-2 infection on the laboratory and clinical outcomes of ART have not yet been consistently documented in the literature [14,[29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 is still evolving [1], resulting in new cases and reinfections in the population [2][3][4]. As SARS-CoV-2 is a new virus, we still need to improve our understanding of it, especially its effects on human reproduction and assisted reproductive technology (ART) [5] Currently, it is believed that the SARS-CoV-2 virus damages cells or tissues by infecting and replicating in cells, which requires the expression of SARS-CoV-2 receptors, such as angiotensin converting enzyme 2 (ACE2), basigin (BSG), transmembrane serine protease 2 (TMPRSS2) and cathepsin L (CTSL) [6,7]. It is noteworthy that all the aforementioned viral receptor mRNAs are expressed in most of the human female reproductive tract, including the ovaries (including follicular granulosa cells) [8] and endometrium [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) Omicron sublineages, such as XBB.1, exhibit enhanced antibody evasion, presenting a significant challenge in the prevention and treatment of COVID‐19 1 . Furthermore, it is essential to understand the effect of COVID‐19 on the reproductive system because it affects fertility policies in multiple regions 2 …”
Section: Introductionmentioning
confidence: 99%
“…1 Furthermore, it is essential to understand the effect of COVID-19 on the reproductive system because it affects fertility policies in multiple regions. 2 Multiple studies have suggested that COVID-19 might influence female reproductive characteristics, including the menstrual cycle, ovarian reserve, and sex hormone levels. 3,4 Two observational studies reported that 28% and 16% of female patients with COVID-19 experienced irregular menstruation respectively, which was associated with disease severity.…”
Section: Introductionmentioning
confidence: 99%